1999
DOI: 10.1126/science.285.5432.1408
|View full text |Cite
|
Sign up to set email alerts
|

Altered Cochlear Fibrocytes in a Mouse Model of DFN3 Nonsyndromic Deafness

Abstract: DFN3, an X chromosome-linked nonsyndromic mixed deafness, is caused by mutations in the BRN-4 gene, which encodes a POU transcription factor. Brn-4-deficient mice were created and found to exhibit profound deafness. No gross morphological changes were observed in the conductive ossicles or cochlea, although there was a dramatic reduction in endocochlear potential. Electron microscopy revealed severe ultrastructural alterations in cochlear spiral ligament fibrocytes. The findings suggest that these fibrocytes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
153
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(162 citation statements)
references
References 15 publications
8
153
0
1
Order By: Relevance
“…The Brn4 null phenotype has been previously described (Minowa et al 1999;Phippard et al 1999). However, our analysis uncovered many additional defects.…”
Section: Fig 1 Defects In Mesenchymal Structures Of Mutant Mice a supporting
confidence: 57%
See 2 more Smart Citations
“…The Brn4 null phenotype has been previously described (Minowa et al 1999;Phippard et al 1999). However, our analysis uncovered many additional defects.…”
Section: Fig 1 Defects In Mesenchymal Structures Of Mutant Mice a supporting
confidence: 57%
“…Previous reports of Brn4 null mice revealed alterations in the expression of key proteins in spiral ligament fibrocytes that likely contribute to the hearing loss found in these mutants (Minowa et al 1999;Xia et al 2002). Consistent with this, Brn4−;Tbx1+/− mice in this study were found to have profound hearing loss by auditory brain-stem response testing at 3 months of age (not shown).…”
Section: Abnormal Spiral Ligament Fibrocytes In Mutant Micementioning
confidence: 94%
See 1 more Smart Citation
“…On the other hand, selective damage to the lateral wall, in the absence of organ of Corti damage clearly can have important effects on hearing levels. For example, in a mouse model of DFN3, with targeted deletion of the BRN-4 gene, there is normal hair cell and spiral ganglion cell development associated with abnormalities in type I, II, and III fibrocytes (Minowa et al 1999). In these mice, EP is decreased and ABR thresholds are elevated.…”
Section: Dynamics Of Cochlear Damage and Associated Changes In Ep Aftmentioning
confidence: 99%
“…RNA in situ hybridization was performed as described (Minowa et al 1999). Digoxygenin labelled riboprobes were synthesized by using the following murine cDNAs: 1.0-kb Pax1, 290-bp Pax9 (kindly provided by Dr K. Imai, GSF-Research Center for Environment and Health, Neuherberg, Germany), 1.1-kb MFH-1 (kindly provided by Dr N. Miura, Akita University, Akita, Japan), 400-bp Col2a1, 440-bp Col9a2, 360-bp Col11a2, 470-bp aggrecan (kindly provided by DrBenoit de Crombrugghe, University of Texas, MD Anderson Cancer Center, Houston, TX), 300-bp Col10a1 (kindly provided by K. S. E. Cheah, Hong Kong University, Hong Kong, China), 1.2-kb osteopontin (kindly provided by Dr S. Nomura, Osaka University, Osaka, Japan), and 450-bp Hox11 (kindly provided by Dr S. J. Korsmeyer, Harvard Medical School, Boston, MA).…”
Section: Cell Proliferation and Apoptosis Assaysmentioning
confidence: 99%